P-OGC04 Evaluation of post-operative surveillance strategies for oesophago-gastric cancers in the United Kingdom. (16th December 2021) - Chidambaram, Swathikan; Sounderajah, Viknesh; Maynard, Nick; Underwood, Tim; Markar, Sheraz
Abstract: Background: Oesophago-gastric malignancies are associated with a high recurrence rate, yet there is a lack of evidence to inform guidelines for the standardisation and structure of post-operative surveillance after curatively intended treatment. This study aimed to capture the variation in post-operative surveillance strategies across the United Kingdom and Ireland, and enquire the opinions and beliefs around surveillance from practicing clinicians. Methods: A web based survey consisting of forty questions was sent to surgeons or allied health professionals performing or involved in surgical care for oesophago-gastric cancers at high volume centers in the United Kingdom (UK). Respondents from each centre completed the survey on what best represented their centre. The first section of the survey evaluated the timing and components of follow-ups, and their variation between centres. The second section evaluated respondents perspective on how surveillance can be structured. Results: Thirty five surgeons from 25 centers consisting 28 consultants, 6 senior trainees and 1 specialist nurse had completed the questionnaire. 45.7% of responders arranged clinical follow-up at 2-4 weeks. Twenty responders had a specific post-operative surveillance protocol for their patients. Of these, 31.4% had a standardised protocol for all patients, while 25.7% tailored it to patient needs. Patient preference, comorbidities and chance of recurrence were considered as major factors for necessitating more intense surveillance than currently practised. Conclusions: There is a significant variation in how patients are monitored after surgery between centers in the UK. Randomised controlled trials are necessary to link surveillance strategies to both survival outcomes and quality of life of patients and to evaluate the prognostic value of different post-operative surveillance strategies.